2016
DOI: 10.1016/j.giq.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Reusing social media information in government

Abstract: Across policy domains, government agencies evaluate social media content produced by third parties, identify valuable information, and at times reuse information to inform the public. This has the potential to permit a di versity of social media users to be heard in the resulting information networks, but to what extent are agencies relying on private citizens or others outside of the policy domain for message content? In order to examine that question, we analyze the online practices of state level government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 37 publications
2
37
0
3
Order By: Relevance
“…Finally, Wukich and Mergel [74] performed an analysis of 8671 tweets among government agencies and found that nearly 35% of the posts were retweets for the purposes of informing and educating the public. The researchers concluded that these agencies reused information since they considered the sources of the data reliable and useful.…”
Section: Reposting (Rt)mentioning
confidence: 99%
“…Finally, Wukich and Mergel [74] performed an analysis of 8671 tweets among government agencies and found that nearly 35% of the posts were retweets for the purposes of informing and educating the public. The researchers concluded that these agencies reused information since they considered the sources of the data reliable and useful.…”
Section: Reposting (Rt)mentioning
confidence: 99%
“…These findings are in line with more in‐depth analytical approaches to the interactions between organizational postings and reactions from citizens to the content. For example, Wukich and Mergel () find that government organizations rarely reuse social media information beyond their trusted and vetted sources. They measure reuse as the type of information that is retweeted from other government organizations or nonprofits that work in the same space.…”
Section: The State Of Social Media Measurement In the Public Sectormentioning
confidence: 99%
“…In practice, government adoption of social media as a monitoring mechanism depends not only on whether valuable information can be identified from social media, but also various factors such as the trustworthiness of data contributors and the organization's culture with respect to adapting to new technologies [8,15]. Future work will examine the case study findings further by interviewing local government professionals.…”
Section: Implications For Using Geosocial Media To Understand Public mentioning
confidence: 99%
“…In addition, social media often contain information about public opinions and perceptions that is comparable to public comments collected through traditional public participation approaches [6]. It may potentially become a more convenient form of public participation as people are able to contribute information at any time from any location [7,8]. Geotagged social media, also referred to as geosocial media [9,10], contain both descriptive comments and location information and thus may assist in understanding what the public needs are and where solutions need to be developed [11,12].…”
Section: Introductionmentioning
confidence: 99%